The impact of COVID-19 on the workplace wellbeing of police services in Australia. (2nd January 2022) - Bamberry, Larissa; Neher, Alain; Jenkins, Stacey; Sutton, Clare; Frost, Mark; Roberts, Russell; Dwivedi, Abhishek; OMeara, Peter; Wong, Alfred
ABSTRACT: Workplace wellbeing is a fast-developing subject in employment relations. This qualitative study examined the workplace wellbeing of police during COVID-19. There has been a significant critique of the narrow focus only on individual resilience and stress as the cause of workers' poor mental health and wellbeing. Research into frontline workers' mental health and wellbeing has mainly focused on the cumulative effect of trauma and operational stress injuries on individual resilience, with insufficient consideration of the impact of organisational culture, systemic and environmental factors. Drawing on a survey of 665 police professionals from all states and territories in Australia, this research investigated individual, the nature of work, organisational and environmental factors that negatively impacted worker wellbeing during the pandemic. The paper concludes that incorporating the full range of factors related to workplace wellbeing would inform an improved, holistic approach to maintaining and enhancing employee wellness. Understanding the influence of these factors during COVID-19 has implications for employment relations theory and the practical management of frontline emergency service workers' workplace wellbeing generally and in times of crisis and disruption.